Effects of vitamin D supplementation on muscle strength in middle-aged and elderly individuals: a retrospective, propensity score-matched study - Qi, Peiyao; Fu, Xiaomin; Zhao, Dan; Li, Chunlin; Lu, Yanhui; Li, Nan (Frontiers in Nutrition, 2024)
Introduction The aim of this study is to investigate the impact of vitamin D supplementation on the muscle strength of the elderly. Methods This retrospective, propensity score-matched study included 160 middle-aged and elderly individuals from a community in Beijing, China. The control group (n=110) received health education and lifestyle guidance, while the intervention group (n=50) was given oral vitamin D supplementation in addition to health education and lifestyle guidance. All participants underwent laboratory tests, muscle function, and physical function at baseline and follow-up. Results In the propensity score-matched cohort of 41 patients per group, the levels of serum calcium and 25-hydroxyvitamin D in both groups were improved significantly by the end of the study (p<0.05), with the intervention group showing a more significant improvement. The muscle strength of the left lower limb in the intervention group significantly increased after the intervention (p<0.05). The results also showed that the grip strength and pinch strength of the patients in both groups increased after the intervention, and the difference between the two groups was statistically significant (p<0.05). Discussion The findings of this study suggest that vitamin D supplementation, in conjunction with lifestyle guidance and health education, is beneficial for enhancing the upper and lower limb strength of patients.